2020
DOI: 10.1519/jsc.0000000000003457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Static Stretching Duration on Muscle Blood Volume and Oxygenation

Abstract: 2022-Muscle blood volume increases due to stretching; however, the minimum duration of stretching to sustainably increase the muscle blood volume after stretching has not yet been elucidated. This study examined whether the duration of static stretching influenced the muscle blood volume and oxygenation. Ten healthy male subjects participated in this controlled laboratory study. Static stretching of the gastrocnemius muscle was performed for 5 durations (20 seconds, and 1, 2, 5, and 10 minutes). Changes in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…After static stretching, there were no significant increases in THb and StO 2 of muscle as well as tendon. Previous studies reported that blood volume (from near-infrared spectroscopy) and blood flow (from ultrasound Doppler) were significantly higher than at rest until about 10 min after the end of static stretching [ 2 4 , 7 ]. In this study, since the foot angle at the beginning and end of stretching was changed manually with the attachment, it was impossible to identify the exact beginning and end points of stretching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After static stretching, there were no significant increases in THb and StO 2 of muscle as well as tendon. Previous studies reported that blood volume (from near-infrared spectroscopy) and blood flow (from ultrasound Doppler) were significantly higher than at rest until about 10 min after the end of static stretching [ 2 4 , 7 ]. In this study, since the foot angle at the beginning and end of stretching was changed manually with the attachment, it was impossible to identify the exact beginning and end points of stretching.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that tendon blood volume continued to increase up to 35 min due to 60 min of heating stimulation, whereas muscle blood volume showed no increase after 20 min [ 13 ]. Therefore, the minimum time for increasing the tendon blood volume may be longer than the minimum time for increasing the muscle blood volume presented by Matsuo et al [ 4 ]. If tendon blood circulation is increased after stretching, stretching may be useful as a maintenance method to increase tendon blood circulation because it does not require special tools.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The oxygenated form of hemoglobin (oxyhemoglobin) has a peak absorption at 850–900 nm, and the deoxygenated form of hemoglobin (deoxy‐hemoglobin) has a peak absorption at 730–750 nm [24]. The detection depth was about 1.25 cm [25]. The concentration changes (post‐cupping—pre‐cupping muscle hemodynamic responses) in oxyhemoglobin (HbO2), deoxy‐hemoglobin (Hb), blood volume (HbO2+Hb), and oxygenation (HbO2Hb) were reported in this study [22].…”
Section: Instrumentationmentioning
confidence: 99%